Lexical Cohesion in English and Persian Texts of Novels - Rahimi, Ali; Ebrahimi, Nabi A. (Mediterranean Journal of Social Sciences, 2012)
What are the stylistic differences between Persian and English novelists with regard to their choices and application of lexical patterns? What are the textual differences between Persian and English novels in terms of lexical cohesion? To answer these questions, two Persian (The Blind Owl by Sadigh Hedayat and The Patient Stone by Sadigh Chubak) together with two English novels (The Old Man and the Sea by Ernest Hemingway and The Pearl by John Steinbeck) which are enormously popular in contemporary Persian and English literatures were selected as the main source of data. The results of lexical cohesion analysis on 1000-word excerpts of these novels showed that the difference between Persian and English novelists’ choices of lexical patterns is caused by the higher number of reiteration as well as the collocation pairs used by Persian novelists. This study concludes that some lexical relations are more frequent in the Persian novels than in the English ones (e.g. Equivalence and Elaborative collocation), conversely some are more salient in English texts under study (e.g. Simple repetition). The similarities of these texts with regard to the frequency of lexical relations turned out to be more than their differences nonetheless. In addition, detailed explanations of the results as well as complete elucidation of the model of analysis (proposed by Tanskanen, 2006) accompanied by examples extracted from the selected Persian and English novels have been put forward. The results of this study can inspire literary critics, theorists in stylistics, EFL teachers, assessment specialists, translators and contrastivists.